1994
DOI: 10.1128/mcb.14.3.1986
|View full text |Cite
|
Sign up to set email alerts
|

Rous sarcoma virus RNA stability requires an open reading frame in the gag gene and sequences downstream of the gag-pol junction.

Abstract: The intracellular accumulation of the unspliced RNA of Rous sarcoma virus was decreased when translation was prematurely terminated by the introduction of nonsense codons within its 5' proximal gene, the gag gene. Subcellular fractionation of transfected cells suggested that nonsense codon-mediated instability occurred in the cytoplasm. Analysis of constructs containing an in-frame deletion in the nucleocapsid domain ofgag, which prevents interaction between the Gag protein and viral RNA, showed that an open r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 23 publications
3
64
0
Order By: Relevance
“…Previous results have shown that termination codons placed throughout the gag coding region destabilize the unspliced RSV transcript (Barker and Beemon 1991) by the NMD pathway (LeBlanc and Beemon 2004). Knowing that the pol gene is translated much less frequently than gag (Swanstrom and Wills 1997), we asked whether termination codons in pol would cause degradation of the unspliced RNA.…”
Section: Translation Of Ptcs In Pol Destabilize the Unspliced Rnamentioning
confidence: 99%
See 4 more Smart Citations
“…Previous results have shown that termination codons placed throughout the gag coding region destabilize the unspliced RSV transcript (Barker and Beemon 1991) by the NMD pathway (LeBlanc and Beemon 2004). Knowing that the pol gene is translated much less frequently than gag (Swanstrom and Wills 1997), we asked whether termination codons in pol would cause degradation of the unspliced RNA.…”
Section: Translation Of Ptcs In Pol Destabilize the Unspliced Rnamentioning
confidence: 99%
“…This deletion prevents packaging of the viral unspliced RNA. Barker and Beemon (1994) reported that a termination codon placed early in the pol gene (nt 2598) had no substantial effect on unspliced RNA stability. However, this could be due to the infrequent À1 frameshift, which leads to infrequent translation of the pol gene.…”
Section: Translation Of Ptcs In Pol Destabilize the Unspliced Rnamentioning
confidence: 99%
See 3 more Smart Citations